2020
DOI: 10.1038/s41598-020-76459-7
|View full text |Cite
|
Sign up to set email alerts
|

A fast and fully-automated deep-learning approach for accurate hemorrhage segmentation and volume quantification in non-contrast whole-head CT

Abstract: This project aimed to develop and evaluate a fast and fully-automated deep-learning method applying convolutional neural networks with deep supervision (CNN-DS) for accurate hematoma segmentation and volume quantification in computed tomography (CT) scans. Non-contrast whole-head CT scans of 55 patients with hemorrhagic stroke were used. Individual scans were standardized to 64 axial slices of 128 × 128 voxels. Each voxel was annotated independently by experienced raters, generating a binary label of hematoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…The above-mentioned results published in this Research Topic confirm the great potential of machine learning methods to improve various aspects of neuroimaging (1). Applications of artificial methods to diagnostic neuroradiology are really only emerging and have a bright future (2), in particular to assist the neuroradiologists in tedious tasks such as the segmentation of multiple sclerosis (3) or stroke (4) lesions, or to help in the emergency room setting, for example in detecting hemorrhage on non-contrast CT (5).…”
Section: Editorial On the Research Topic Machine Learning In Neuroimagingsupporting
confidence: 60%
“…The above-mentioned results published in this Research Topic confirm the great potential of machine learning methods to improve various aspects of neuroimaging (1). Applications of artificial methods to diagnostic neuroradiology are really only emerging and have a bright future (2), in particular to assist the neuroradiologists in tedious tasks such as the segmentation of multiple sclerosis (3) or stroke (4) lesions, or to help in the emergency room setting, for example in detecting hemorrhage on non-contrast CT (5).…”
Section: Editorial On the Research Topic Machine Learning In Neuroimagingsupporting
confidence: 60%
“…Recently, deep learning has shown many encouraging results in the field of medical image processing and analysis. Particularly, a convolutional neural network (CNN) has been shown to be well suited for object detection 11 , 12 , semantic segmentation 13 , 14 , image classification 15 , 16 , and prediction 17 , 18 tasks in radiological research. This study aimed to develop a CNN-based method using chest and abdominal CT scout images for predicting body weight and to evaluate the correlation between actual and predicted body weights.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [ 97 ] reported a hybrid 3D/2D mask ROI-based CNN framework with efficient hematoma detection, classification, and segmentation capabilities in parallel. Arab et al [ 98 ] presented a deep learning model with deep supervision for quick and automated segmentation of whole-head CT. Desai et al [ 99 ] presented a deep learning model using pre-trained Google Net to detect the presence of basal ganglia hematoma in a dataset consisting of 170 CT images. Hssayeni et al [ 100 ] proposed a fully automated U-Net model for segmentation of hematoma regions from 82 CT scans.…”
Section: Generics Of Computer Aided Diagnosismentioning
confidence: 99%
“…Chang et al [ 97 ] developed a novel hybrid ROI-based CNN to estimate the 3D volumes of IPH, SDH, and EDH, respectively. Arab et al [ 98 ] presented a CNN model with deep supervision (CNN–DS) to perform hematoma quantification on whole-head CT rapidly and more efficiently. Jain et al [ 114 ] developed a U-Net based CNN model to compute the volume of acute hematoma lesions, and validated their technique using a multi-centre dataset.…”
Section: Generics Of Computer Aided Diagnosismentioning
confidence: 99%